Komik Digital Sistem Peredaran Darah dan Pengaruhnya Pada Literasi Sains Peserta Didik - Berti Yolida; Rini Rita T Marpaung; Ni Made Ari Rusadi (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2022)
This study aims to determine the effect of using digital comics on the scientific literacy of class VIII students on the human circulatory system at SMP Negeri 3 Natar. The research sample of 32 students in class VIIIA as the experimental class and 32 students in class IIC as the control class were selected using a purposive sampling technique. The research design used a quasi-experimental non-equivalent control group design. The type of data used is quantitative data in the form of scientific literacy test questions and qualitative data using students' responsibility questionnaires for digital comics. The results showed that the value of Sig. (2-tailed) 0.000 0.005 so that H1 is accepted and H0 is rejected, so the use of digital comics has a significant effect on students' scientific literacy. Student responses in this study were in the good category (80%).Keywords: scientific literacy, digital comics, students Penelitian ini bertujuan untuk mengetahui pengaruh pemanfaatan komik digital terhadap literasi sains peserta didik kelas VIII materi sistem peredaran darah manusia di SMP Negeri 3 Natar. Sampel penelitian sebanyak 32 peserta didik kelas VIIIA sebagai kelas eksperimen dan 32 peserta didik kelas VIIIC sebagai kelas kontrol dipilih menggunakan teknik purposive sampling. Desain penelitian ini menggunakan quasi eksperimental tipe non-equivalent control grup design. Jenis data yang digunakan yaitu data kuantitatif dalam bentuk soal tes literasi sains dan data kualitatif dengan angket responsibility peserta didik terhadap komik digital. Hasil penelitian menunjukkan bahwa nilai Sig. (2-tailed) 0,000 0,005 sehingga H1 diterima dan H0 ditolak, sehingga penggunaan komik digital berpengaruh signifikan terhadap literasi sains peserta didik. Respon siswa dalam pembelajaran ini berkategori baik (80%). Kata kunci: literasi sains, komik digital, peserta didik DOI: http://dx.doi.org/10.23960/jbt.v10.i3.25898